STUDENT ENGAGEMENT AS A MEDIATOR IN TEAM-BASED PROJECT–BASED COLLABORATIVE DIGITAL LEARNING ON STUDENT LEARNING OUTCOMES - rita, Mutiarni; Purwanto, Nuri; Nusron, Anis (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2025)
The digital transformation of higher education requires learning models that are capable of enhancing student engagement and learning outcomes. This study aims to examine the effect of collaborative digital learning based on the Team-Based Project (TBP) approach implemented through the SPADA Indonesia platform on student learning outcomes, with student engagement acting as a mediating variable. This research employed a quantitative approach using a survey design. The respondents consisted of 69 undergraduate management students who participated in a collaborative Innovation Management course jointly conducted by STIE PGRI Dewantara Jombang and the Yadika Institute of Technology and Business Pasuruan. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and path analysis. The results indicate that TBP-based collaborative digital learning has a positive and significant effect on both student engagement and student learning outcomes. Furthermore, student engagement was found to significantly mediate the relationship between collaborative digital learning and learning outcomes. These findings suggest that optimizing SPADA Indonesia through a Team-Based Project approach is effective in improving the quality of learning in higher education.